1982
DOI: 10.1128/iai.36.1.184-188.1982
|View full text |Cite
|
Sign up to set email alerts
|

Protection of mice from infection with Streptococcus pneumoniae by anti-phosphocholine antibody

Abstract: Anti-phosphocholine (PC) antibody mediated protection against many strains of Streptococcus pneumoniae, and hybridoma anti-PC antibodies protected mice from fatal infections with types 1 and 3 S. pneumoniae. Live types 1, 3, 5, 6A, and 19F S. pneumoniae had similar amounts of surface PC accessible to antibody. Furthermore, mice expressing the X-linked immunodeficiency (xid) of the CBA/N strain were found to be more susceptible to infection with S. pneumoniae of types 3, 6A, and 19F than were immunologically no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
2

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 19 publications
4
59
2
Order By: Relevance
“…X-linked immunodeficiency affects resistance to several infections. Thus, CBA/N mice are highly susceptible to infection with different strains of type 3 Streptococcus pneumoniae [39,40], Giardia muris [41], Plasmodium yoelli [42], Pseudomonas aeruginosa [43], and Salm. typhimurium [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…X-linked immunodeficiency affects resistance to several infections. Thus, CBA/N mice are highly susceptible to infection with different strains of type 3 Streptococcus pneumoniae [39,40], Giardia muris [41], Plasmodium yoelli [42], Pseudomonas aeruginosa [43], and Salm. typhimurium [44].…”
Section: Discussionmentioning
confidence: 99%
“…Highly susceptible to Salmonella, (CBA/N 2 DBA=2) F 1 males (xid hemizygous) were characterized by low titre of anti-salmonella IgG antibodies after immunization with a preparation of killed bacteria, whilst the level of T cell reaction in F 1 male and female mice was similar [44]. Xidbearing mice could be protected by injection of normal sera from mice with the wild type xid allele [40,44].…”
Section: Discussionmentioning
confidence: 99%
“…Using '251-labelled antibodies against the PC-determinant, Yother ef al. (40) showed that PnC was accessible on the surface of live types 1, 3, 5, 6A and 19F pneumococci. The binding of antibodies was, however, much more efficient with an unencapsulated strain, indicating, according to the authors, that capsules were highly, but not completely, effective in masking the cell-wall-associated PC determinants.…”
Section: Discussionmentioning
confidence: 99%
“…The PC residue is bound at the 6th position of the galactosamine. The PnC has been demonstrated by chemical or immunological techniques in a great number of capsular types of pneumococci, and it is considered to be species-specific (7, 16,26,30,40). Cross reactions between pneumococci and a-streptococci with monoclonal anti-PC antibodies were shown to depend on the occurrence of PC determinants on the a-streptococci (27).…”
Section: Discussionmentioning
confidence: 99%
“…Mortality was recorded 14 days after exposure. The LD50 was determined by the method of [19] with slight modification.…”
Section: Infection Of Mice With Streptococcus Pneumoniae Of Minimum Lmentioning
confidence: 99%